Geographies of the internet - Warf, Barney, 1956- (Milton Park, Abingdon, Oxon; New York, NY: Routledge, 2020)
"This book offers a comprehensive overview of recent research on the internet, emphasizing its spatial dimensions, geospatial applications, and the numerous social and geographic implications such as the digital divide and the mobile internet. Written by leading scholars in the field, the book sheds light on the origins and the multiple facets of the internet. It addresses the various definitions of cyberspace and the rise of the World Wide Web, draws upon the media theory, as well as explores the physical infrastructure such as the global skein of fibre optics networks and broadband connectivity. Several economic dimensions, such as e-commerce, e-tailing, e-finance, e-government, and e-tourism are also explored. Apart from its most common uses such as Google Earth, social media like Twitter, and neogeography, this volume also presents internet's novel uses for ethnographic research and the study of digital diasporas. Illustrated with numerous graphics, maps and charts, the book will best serve as supplementary reading for academics, researchers, and as a professional handbook for policy makers involved in communications, media, retailing, and economic development"-- Includes bibliographical references and index. "This book offers a comprehensive overview of recent research on the internet, emphasizing its spatial dimensions, geospatial applications, and the numerous social and geographic implications such as the digital divide and the mobile internet. Written by leading scholars in the field, the book sheds light on the origins and the multiple facets of the internet. It addresses the various definitions of cyberspace and the rise of the World Wide Web, draws upon the media theory, as well as explores the physical infrastructure such as the global skein of fibre optics networks and broadband connectivity. Several economic dimensions, such as e-commerce, e-tailing, e-finance, e-government, and e-tourism are also explored. Apart from its most common uses such as Google Earth, social media like Twitter, and neogeography, this volume also presents internet's novel uses for ethnographic research and the study of digital diasporas. Illustrated with numerous graphics, maps and charts, the book will best serve as supplementary reading for academics, researchers, and as a professional handbook for policy makers involved in communications, media, retailing, and economic development"--